2017
DOI: 10.3390/polym9070247
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Chitosan/Soy Protein Isolate Nanocomposite Film Reinforced by Cu Nanoclusters

Abstract: Soy protein isolate (SPI) based films have received considerable attention for use in packaging materials. However, SPI-based films exhibit relatively poor mechanical properties and water resistance ability. To tackle these challenges, chitosan (CS) and endogenous Cu nanoclusters (NCs) capped with protein were proposed and designed to modify SPI-based films. Attenuated total reflectance-Fourier transform infrared spectroscopy and X-ray diffraction patterns of composite films demonstrated that interactions, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…The first stage from 120 to 280°C was mainly attributed to the glycerol degradation . The second stage was from 280 to 450°C, which could be associated with the decomposition of protein backbone . As summarized in Table , the T max1 value of the SPI/G/PCNTs film was higher than that of the neat SPI film.…”
Section: Resultsmentioning
confidence: 93%
“…The first stage from 120 to 280°C was mainly attributed to the glycerol degradation . The second stage was from 280 to 450°C, which could be associated with the decomposition of protein backbone . As summarized in Table , the T max1 value of the SPI/G/PCNTs film was higher than that of the neat SPI film.…”
Section: Resultsmentioning
confidence: 93%
“…At the fifth day, the h • were lower than the initial value, the FO3 coated samples showed the highest h • values. The decrease in h • of blueberries was mainly caused by the degradation of anthocyanins during ripening [20]. It indicated that FODF could retard the maturation of blueberries and slow down the decrease of h • .…”
Section: Freeh-keeping Properties Of Filmsmentioning
confidence: 93%
“…The surface color of blueberries were measured using a colorimeter. a and b parameters from CIE Lab scale were recorded and Hue angles (h • ) index was calculated [20]:…”
Section: Color Of the Blueberry Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominant amino acids present in whey were leucine, isoleucine, lysine, tyrosine, cysteine, valine, threonine, tryptophan and histidine [23]. SPI a cheap plant protein of renewable resource, is safe and has good film-forming ability, and biocompatibility [25]. It is widely used as food ingredients owing to their high nutritional and excellent functional properties [26].…”
Section: Introductionmentioning
confidence: 99%